The limitations of accommodation the changing legal context of religion at work in the United States - Phipps, Kelly A. (2019)
Other authors have warned that the legal standard of accommodation is insufficient as a strategy for practicing managers leading religiously and spiritually diverse workforces. Recent changes in the legal context of faith at work have only amplified those concerns. This article examines the adoption of state laws known as Religious Freedom Restoration Acts, or RFRA's, as well as the US Supreme Court ruling in Burwell v. Hobby Lobby. Both of these changes exacerbate the concerns previously articulated, and illustrate the limitations of using the legal standard of accommodation as a management strategy for negotiating diverse religious and spiritual expression in the workplace. The nature of these two developments is explained, together with a discussion of their significance for practitioners and researchers in the field of management, spirituality, and religion (MSR).
Keywords: religious accommodation; United States Supreme Court; free exercise clause; Religious Freedom; religious accommodation; free exercise clause; United States Supreme Court; Religious Freedom; Aufsatz in Zeitschrift